Experimental Detection of Transformer Excitation Asymmetry through the Analysis of the Magnetizing Current Harmonic Content - Pjevalica, Nebojsa; Petrovic, Nenad; Pjevalica, Velibor; Teslic, Nikola (Elektronika ir Elektrotechnika, 2016)
The presence of a low DC voltage in a power grid produces an excitation asymmetry for the distribution transformers, resulting in unwanted half-cycle saturation that may impair transformer safety, reliability and efficiency, especially in increasing the reactive power, stray losses and iron losses. This paper highlights a diagnostic method based on the phase value of the particular even harmonics of a transformer excitation current as the basic marker of an excitation asymmetry. In order to achieve a straightforward insight into the nature of even harmonics behaviour, a novel method of decomposition an excitation current waveform into its unhysteretic (pure magnetization) and hysteretic components has been included in the harmonic analysis. DOI: http://dx.doi.org/10.5755/j01.eie.22.2.14590